Taxonomic and phylogenetic evidence reveal a new species and a new record of the genus Marasmius (Marasmiaceae) from Pakistan - Asif, Muhammad; Maula, Fazli; Saba, Malka; Akram, Wajahat; Raza, Mubashar (Phytotaxa, 2024)
This research reveals a significant contribution to fungal taxonomy through the integration of morphological and phylogenetic analyses, utilizing ITS and 28S sequences. Focused on the Marasmius genus in Pakistan, the combined approach has successfully identified a new species, namely M. pakistanicus, and a new record, M. paratrichotus. The new species is characterized by its small orange pileus with a grooved surface, creamy lamellae, lacrymoid to subcylindrical basidiospores, broadly clavate cheilocystidia, and a hymeniderm pileipellis composed of inconspicuous or broadly clavate elements. This study enhances our knowledge of fungal diversity by scrutinizing both morphological traits and genetic profiles. The morphological and phylogenetic analyses based on the combined ITS-28S dataset confirmed that both species belong to the Marasmius sect. Sicci. These findings not only broaden our understanding of local fungal biodiversity but also underscore the efficacy of a comprehensive methodology. They emphasize the synergy between morphology and phylogenetics as instrumental in advancing our knowledge of fungal communities.